Clinicopathological Significance of Tumor Budding in Breast Carcinoma - Buch, Archana; Jain, Khushi; Rathod, Hetal; Gore, Charusheela (Journal of Nepal Health Research Council, 2024)
Background: Tumour budding Tuberculosis is a new prognostic marker whose role in breast cancer is still under evaluation. Our aim was to study Tuberculosis in breast carcinoma and correlate it with other prognostic markers.Methods: A descriptive cross-sectional study was conducted over 2 years on 75 invasive breast carcinoma specimens and biopsies. Hematoxylin and Eosin sections were examined for tumour grade, stage, molecular subtype, necrosis, lymphovascular invasion inflammation and counting of Tuberculosis. Lymph node metastasis was studied only in mastectomies. TB was defined as a cluster of 1-5 tumour cells and counted in 10 consecutive 400X fields. The cut-off for high grade TB was taken as ?10 per 10 HPFs. Immunohistochemical staining was done for molecular subtyping and differentiating Tuberculosis from mimickers. Statistical analysis was done using chi square test and Fischer’s exact test.Results: Tuberculosis was present in 66/75 cases; 53% (n=35) were high grade. Among these, majority were of T2 (74%, n= 26), grade 2 (52%, n= 18), luminal A (34%, n= 12), had 3+ inflammation (46%, n= 16) and peripheral tumour buds (54%). Necrosis and lymphovascular invasion were absent in 77% and 71%, respectively. Lymph node metastasis was seen in 63% (n= 25/28) cases. Statistically significant association (p= 0.016) was observed between degree of inflammation and Tuberculosis grade. However, no significant association was observed between TB and other prognostic markers of breast carcinoma.Conclusions: In our study, association of Tuberculosis with different prognostic markers was appreciated but was not statistically significant. However, it highlights need for standardization of Tuberculosis reporting.Keywords: Breast Neoplasms; epithelial-mesenchymal transition; prognosis; tumor budding.